Combining ability and heterosis in single crosses derived from some local maize (Zea mays L.) inbred lines - Elali Elkhalf, Ahmad; Ali, Eltahir; Meseka, Silvestro; Ibrahim, Abu Elhassan (Gezira Journal of Agricultural Science; Vol 8 No 1 (2010), 2010)
This study was conducted to assess the grain yield , combining ability and heterosis of some local maize ( Zea mays L.) inbred lines and then hybrids. Experiments were carried out during autumn in 2008 at Gezira Research Station (GRS) and Matuq Research Station (MRS) of the Agricultural Research Corporation (ARC), Sudan, in a randomized complete block design with three replications. Combining ability was studied among 8 (4 white and 4 yellow) local inbred lines of maize and their 28 F 1 crosses. Most of the parents were late flowering except L-11 and L-12. Results of mean grain yield performance showed that crosses L-11×L-7 and L-14×L-7 were the best at GRS with means of 6229 and 6147 kg ha, respectively; while at MRS, crosses L-14× L-3 and L-7× L-1 were the best with mean grain yields of 3929 and 3860 kg/ha, respectively. Combined analysis of variance across sites identified L-3×L-7 and L-14×L-7 as the top grain yielders coupled with earliness and short plant height. Combining ability analysis revealed that non-additive genetic effects were more important for the measured traits. Lines L-7 and L-1 showed the best GCA effects for grain yield and 100 kernels weight in GRS, while L-11 and L-13 in MRS. Lines L-9, L-12 and L-11 were good general combiners for earliness. Maximum heterosis for grain yield (79.2%) was obtained in the cross L-14xL-7 at GRS, while L-14xL-3 at MRS (218.1%). At both locations, crosses L-14xL-7, L-14xL-3, L-1xL-9, L-14xL-9 and L-11xL-3 were the best specific combiners (SCA) for grain yield that associated with good SCA effects and heterotic pattern. Hence, these hybrids could be recommended for further testing in multi-location trails to confirm the consistency of their grain yield.       نفذت هذه الدراسة لتقدير الأداء، القدرة على التوافق وقوة الهجين في سلالات ذرة شامية  محلية ذاتية التلقيح. زرعت التجارب في خريف 2008 في محطتي بحوث الجزيرة ومعتوق، هيئة البحوث الزراعية، السودان. استخدم تصميم القطاعات العشوائية الكاملة مع ثلاث مكررات. درست القدرة على التوافق لـ 8 سلالات (4 بيضاء و 4 صفراء) ذاتية التلقيح و28 هجين ناتج منها من خلال التهجين المتبادل والذي طبق في موسم الخريف، 2007. معظم الآباء كانت متأخرة بالإزهار ما عدا L-11 وL-12. أظهرت الهجن L-11×L-7 وL-14×L7 أفضل أداء للغلة الحبية في محطة بحوث الجزيرة مع متوسطات 6229 و6137 كغ/هـ، على التوالي، بينما في محطة بحوث معتوق L-14×L-3  وL-7×L-1 كانت الأفضل مع متوسطات 3929 و 3860 كغ/هـ، على التوالي. أظهرت الهجن L- 3×L-7  و L-14×L-7 أفضل أداء للغلة الحبية مترافق مع البكور وقصر النبات. التأثيرات الوراثية الغير تراكمية (Non- additive) كانت أكثر أهمية للصفات المدروسة. أظهرت السلالات L-7 و L-1 أفضل قدرة عامة على التوافق للغلة الحبية ووزن الـ 100 حبة في محطة بحوث الجزيرة أما  L-13 وL- 11 في محطة بحوث معتوق. كانت السلالات 9L-، L-12 و L-11 ذات قدرة جيدة عامة على التوافق للبكور. أعطى الهجين  L-14×L7 أفضل قوة هجين ((% 79.2 للغلة الحبية في محطة بحوث الجزيرة وبينما سجل الهجين L-14×L-3 أعلى قوة هجين (% 218.1) في محطة بحوث معتوق. أبدت الهجن L-14×L-7،L-14×L-3 ،L-1×L-9 ،L-14×L-9  وL-11×L-3   أفضل قدرة خاصة على التوافق مترافقة مع أفضل قوة هجين لذلك ينبغي التوصية بتقييمها في مواقع متعددة لتأكد من ثبات أداءها للغلة الحبية.